Lesions in the central amygdala impair sodium intake induced by the blockade of the lateral parabrachial nucleus - Andrade-Franze, Glaucia M. F. [UNESP]; Andrade, Carina A. F.; De Luca, Laurival A. [UNESP]; De Paula, Patricia M. [UNESP]; Colombari, Debora S. A. [UNESP]; Menani, José Vanderlei [UNESP] (Elsevier B.V., 2010)
The blockade of the lateral parabrachial nucleus (LPBN) with the GABAergic receptor agonist muscimol induces strong hypertonic NaCl intake in satiated and normovolemic rats, whereas lesions of the central nucleus of the amygdala (CeA) reduce sodium intake induced by different protocols. In the present study we investigated the effects of bilateral lesions of the CeA on water and 0.3 M NaCl intake induced by GABAergic receptor activation with bilateral injections of muscimol into the LPBN in satiated rats. Male Holtzman rats (n=6-10) with bilateral sham or electrolytic lesions (2 mA; 10 s) of the CeA and stainless steel cannulas implanted bilaterally in the LPBN were used. Bilateral injections of muscimol (0.5 nmol/0.2 mu l) into the LPBN in satiated sham-lesioned rats induced 0.3 M NaCl intake (16.1 +/- 5.4 ml/4 h, vs. saline: 1.3 +/- 0.5 ml/4 h) and water intake (8.1 +/- 3.5 ml/4 h, vs. saline: 1.6 +/- 0.5 ml/4 h). Bilateral lesions of the CeA (3 days) abolished 0.3 M NaCl intake (0.1 +/- 0.1 ml/4 h) and water intake (0.1 +/- 0.1 ml/4 h) induced by bilateral injections of muscimol into the LPBN in satiated rats. The present results show that water and 0.3 M NaCl intake induced by the blockade of LPBN neurons with muscimol depends on the integrity of the CeA, suggesting that facilitatory mechanisms present in the CeA are essential for water and hypertonic NaCl intake that arises after the blockade of the inhibitory mechanisms of the LPBN with muscimol. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Sodium appetite; Parabrachial nucleus; Amygdala; Thirst; Muscimol; GABA